Perancangan Media Pembelajaran Simulasi dan Komunikasi Digital Menggunakan Mit App Inventor di SMKS Kesehatan Paluta Husada - Harahap, Afrina Marito; Musril, Hari Antoni; Supriadi, Supriadi; Okra, Riri (Indonesian Research Journal on Education, 2023)
This research is motivated by Simulation and Digital Communication learning that the learning system still uses books and projectors as media. Where at this time learning processes have begun to be collaborated with electronic learning or called android-based. The purpose of this research is to produce an Android-based learning media design for class XI simulation and digital communication subjects at the Paluta Husada Health Vocational School that is valid, practical, and effective using the MIT APP Inventor and several supporting software. Research on the design of digital communication and simulation learning media using Mit App Inventor uses the Research and Development (R&D) methodusing the Luther-Sutopo multimedia development model, which consists of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The product test used in this study consisted of a validity test, practicality test and effectiveness test. The results of this android-based digital communication and simulation learning media research get a validity test value with an average value of 0.81 with a very valid category, a practicality test with an average value of 0.84 with a very practical category and aneffectiveness test with an average value of 0.84. the average is 0.93 with a very valid category, based on the test results of android-based digital communication and simulation learning media products using the MIT APP Inventor have been valid, practical and effective. So, teachers can use this learning media to attract students' attention to be more diligent in studying because with this media students only open Android and students learn anytime and anywhere.